Syros Metasomatic Tourmaline: Evidence for Very High-δ11B Fluids in Subduction Zones - Marschall H.R.; Ludwig T.; Altherr R.; Kalt A.; Tonarini S. (My University, 2006)
High-pressure (HP) metamorphic blocks enclosed in a mafic to ultramafic matrix from a melange on the island of Syros are rimmed by tourmaline-bearing reaction zones (blackwalls). The B isotopic composition of dravitic tourmaline within these blackwalls was investigated in situ by secondary ion mass spectrometry. Boron in these tourmalines is unusually heavy, with ?11B values exceeding +18‰ in all investigated samples and reaching an extreme value of +28·4‰ in one sample. Blackwalls formed during exhumation of the HP melange at a depth of 20–25 km at temperatures of 400–430°C, by influx of external hydrous fluids. The compositions of the fluids are estimated to be in the range of 100–300 ?g/g B with ?11B values of +18 to +28‰. The high ?11B values cannot be explained by tourmaline formation from unmodified slab-derived fluids. However, such fluids could interact with the material in the exhumation channel on their way from the dehydrating slab to the site of tourmaline formation in the blackwalls. This could produce exceptionally high ?11B values in the fluids, a case that is modelled in this study. The model demonstrates that subduction fluids may be effectively modified in both trace element and isotopic composition during their migration through the material overlying the subducting slab. Blackwall tourmaline from Syros has a large grain size (several centimetres), high abundance, and an exceptionally high ?11B value. The formation of tourmaline at the contact between mafic or felsic HP blocks and their ultramafic matrix involved fluids released during dehydration reactions in the subducting slab. It forms a heavy-boron reservoir in hybrid rocks overlying the subducting slab, and may, thus, have a significant impact on the geochemical cycle of B and its isotopes in subduction zones.